Fear avoidance beliefs in back pain-free subjects are reflected by amygdala-cingulate responses - Meier, Michael L.; Stämpfli, Phillipp; Vrana, Andrea; Humphreys, Barry K.; Seifritz, Erich; Hotz-Boendermaker, Sabina (Frontiers in Human Neuroscience, 2015)
In most individuals suffering from chronic low back pain, psychosocial factors, specifically fear avoidance beliefs, play central roles in the absence of identifiable organic pathology. On a neurobiological level, encouraging research has shown brain system correlates of somatic and psychological factors during the transition from (sub) acute to chronic low back pain. The characterisation of brain imaging signatures in pain-free individuals before any injury will be of high importance regarding the identification of relevant networks for low back pain vulnerability. Fear-avoidance beliefs serve as strong predictors of disability and chronification in low back pain and current research indicates that back pain related fear avoidance beliefs already exist in the general and pain-free population. Therefore, we aimed at investigating possible differential neural functioning between high- and low fear-avoidant individuals in the general population using functional magnetic resonance imaging. Results revealed that pain-free individuals without a history of chronic pain episodes could be differentiated in amygdala activity and connectivity to the pregenual anterior cingulate cortex by their level of back pain related fear avoidance beliefs. These results shed new light on brain networks underlying psychological factors that may become relevant for enhanced disability in a future LBP episode.